Rotating orthogonal polarization imaging - Zhu, Qun (2009)
Non-invasively characterizing the polarization properties of tissues has potential for in vivo clinical applications such as monitoring the healing state of wounds and burns. Conventional methods, which measure the polarization difference of a tissue and usually involve a co-polarized detection, are either restricted by a sample's surface reflections or can only be performed in off-axial systems with the use of matching fluid and a glass plate applied to the sample's surface. In this thesis a new technique called rotating orthogonal polarization imaging (ROPI) is presented.